Commercial Real Estate Prices During COVID-19 : What is Driving the Divergence? - Deghi, Andrea (Global Financial Stability Notes; Global Financial Stability Notes ;, 2022)
After dropping sharply in the early phases of the COVID-19 pandemic, commercial real estate prices are on the mend. However, the initial price decline, as well as the pace of recovery, vary widely across regions and different segments of the commercial real estate market. This note analyzes the factors that explain this divergence using city-level data from major advanced and emerging market economies. The findings show that pandemic-specific factors such as the stringency of containment measures and the spread of the virus are strongly associated with a decline in prices, while fiscal support and easy financial conditions maintained by central banks have helped to cushion the shock. A higher vaccination rate has aided the recovery of the sector, especially in the retail segment. Structural changes in private behavior such as the trend toward teleworking and e-commerce have also had an impact on commercial property prices in some segments. The outlook of the sector across regions thus remains closely tied to the trajectory of the pandemic and broader macroeconomic recovery, financial market conditions, and the pace of structural shifts in the demand for specific property types. In an environment of tightening financial conditions and a slowdown in economic activity, continued vigilance is warranted on the part of financial supervisors to minimize financial stability risks stemming from potential adverse shocks to the sector.